Reliability Improvement Study of a Distribution Network with Distributed Generation - Idowu, Kayode; Uhunmwangho, Roland; Okafor, Ephraim; Big-Alabo, Ameze (Applications of Modelling and Simulation, 2021)
The reliability of power supply to customers is an important factor in the design, planning and operation of a distribution network. This study analyzed the effect of Distributed Generation (DG) on the reliability of distribution network in Port Harcourt metropolis. Five injection substations were used as case studies. Electrical Transient Analyser Programme (ETAP 16.0) was used to model the network using the data collected from the utility company. The reliability of the network was investigated with and without DG units. The reliability of the network improved when DG units were integrated into it at different locations. Multiple integration of DG into network near load points further increased the reliability of the system. The results showed that the utility company can better satisfy their customers with DG in the network and hence increase their revenues. The reliability indicators used for analysis in this study are System Average Interruption Frequency Index (SAIFI), Customer Average Interruption Duration Index (CAIDI), Customer Average Interruption Frequency Index (CAIFI) and Average Service Availability Index (ASAI).